Service Quality, Promotions, and Product Prices on Consumer Purchasing Decisions in the Marketplace: The Mediating Role of Brand Image - Nur Hikmah; Mustari Mustari; Muh Ihsan Said Ahmad; Nur Arisah; Wulan Purnamasari (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2025)
In today's digital era, almost all activities can be carried out using the internet, making information access easier. This study aims to review and analyze existing problems to determine the extent of the influence of service quality, promotions, and product prices in the marketplace on consumers' purchasing decisions, with brand image acting as a mediating variable. The research subjects are students from eight study programs at the Faculty of Economics and Business, Makassar State University, from the 2021 and 2022 intakes, with a sample size of 348 respondents. Data analysis was conducted using the Partial Least Squares Structural Equation Model (PLS-SEM). Based on the problem formulation, the study results show that service quality, promotions, product prices, and brand image have a positive and significant influence on consumers' purchasing decisions. Additionally, brand image effectively mediates the relationship between these three variables and consumers' purchasing decisions.